Server+ Certification Exam Cram 2 (Exam SKO-002) - Brooks, Charles J. (Pearson IT Certification, 2005)
Server+ Exam Cram 2 is an efficient, effective and concise guide that gives you exactly what you need to know to pass the Server+ exam. Organized according to exam objectives, you will be able to quickly and easily assess your understanding of key exam topics. Some of the topics covered are: General Server Hardware Knowledge Configuration Protective Maintenance Troubleshooting and Problem Determination Disaster Recovery Dozens of test-taking strategies are included, as well as timesaving tips and the popular Cram Sheet tearcard, perfect for last-minute studying. The included CD-ROM also gives you access to a MeasureUp practice test engine and a bookmarked, searchable PDF of the book, so you can study without having to take the book with you. Server+ Exam Cram is your smartest way to get certified.